LOGISTICS OPERATIONS WITHIN THE TRANSSHIPMENT IN A CONTAINER PORTS (Perner's Contacts, 2011)
An article analyses all procceding logistics operations in a container port terminals within the transshipment of containers. There are described key elements of each service area as well as the most used technologies and technological equipments. The attention is also concerned to comparison of used equipments in a container port terminals.
Keywords: terminal; container; transshipment